Real-time feedback enhances motor learning and motivation in youth team sports through augmented reality tools - He, Xiaohua; Wei, Li (Frontiers in Psychology, 2025)
IntroductionLive augmented reality (AR) feedback has become a potential tool for the improvement of motor learning and motivation in youth sports. There is, however, minimal information on its combined performance and intrinsic motivation impacts on team sport in ecologically valid conditions. The research question of this study was to determine whether AR-based feedback is more effective in motor skill acquisition and motivation during youth soccer players than coach-based instruction.MethodsSixty trained soccer players aged (12-15) were randomly grouped into an AR feedback group and a control group that had conventional verbal feedback. The three weeks were spent on the same training drills done by the two groups. On the pre-test, post-test, and four-week follow-up, motor performance (dribbling, passing, and shooting) was measured. The validated subscales of the Intrinsic Motivation Inventory were used to assess the motivation. The information on group differences and retention was analyzed by mixed-model ANOVA with Bonferroni adjustments and estimation of the effect size.ResultsThe AR group recorded much greater improvement in all the measured skills, with the most improvement recorded in accuracy when shooting. The intrinsic motivation (interest, perceived competence, and effort) also improved more in the AR group. Motivational improvement was positively correlated with performance gains.DiscussionThe results show that AR feedback in real-time improves motor learning and intrinsic motivation among young athletes. The findings aid the application of AR as a pertinent and interactive instrument of skill development in those sport training settings among young people.